Northwest History. Alaska. Dogs, Dog Races & Mushers. (1936)
Woman Musher Offered Plane. WOMAN MUSHER OFFERED PLANE FAIRBANKS, Alaska, March 3. -- Pilot Herman Lerdahl said he would fly today to Tanana crossing, 165 miles southeast, of here, to bring back Mary Joyce, 27, en route on the last lap of her 1000-mile dog sled journey, if she wants to come. Lerdahl said his plane is large enough to transport Miss Joyce and her five dogs, but not her sled. The comely Twin Glaciers lodge mistress from Taku, B. C, 40 miles southeast of Juneau, left December 20, 1935, for Fairbanks. She is Miss Juneau in the annual Fairbanks ice carnival and dog derby March 5, 6, 7, and 8. Delayed by Weather. Carnival committee members decided to have her flown to Fairbanks so she would arrive in time for the opening. Miss Joyce has been delayed by heavy snows and cold weather. If Miss Joyce accepts the offer she will return after the carnival and complete her journey by dog sled. Late in the day reports from Juneau said an airplane would leave the capitol, if weather permitted, and fly to Fairbanks via Tanana crossing.